Dental profiling in the archaeological sample of the Illyrian population in Southern Dalmatia, Croatia - Marina Marić; Jelena Dumančić; Marin Vodanović; Igor Borzić; Dinko Radić; Davorka Radovčić; Hrvoje Brkić (Homo)
Background: Dental profiling is the process of analyzing teeth to identify a victim or skeletal remains when no antemortem data are available. Using dental profiling techniques, we can determine the age, sex, and population of the individual and gather data about their socio-economic status, personal habits, oral and systemic health, occupation, nutrition, family relationships, and psychological characteristics. Aims: The research aims to gain insights into the diet, health, socio-economic status, and demography of the Late Iron Age inhabitants of Illyrian origin who lived on the Croatian island of Korčula. This will be achieved by analyzing the remains of teeth and jaw bones found in the Kopila necropolis. Material and methods: The research sample comprised 479 permanent teeth and jawbone remains from three tombs that belong to the collection of the Vela Luka Culture Centre on the island of Korčula. The analysis of the teeth included an examination of their morphological and pathological characteristics as well as metric and non-metric variables. Additionally, the stable isotopes of carbon (14C, 13C), nitrogen (15N), and strontium (86/87Sr) were chemically analyzed. Odontometry was used as a metric variable and the Arizona State University Dental Anthropology System (ASUDAS) was used as a non-metric variable to determine sex. Results: The research findings indicate that healthy teeth are present with a frequency of dental caries of 5.85% and tooth wear of 85.18%. There is morphological atypicality in the number of roots of the upper premolars and taurodontism in the molars. Stable isotopes of carbon and nitrogen show values of δ 13C = −19.5‰ (±0.1‰) and δ 15N = 8.6‰ (±0.1‰). The ratio 13C/15N is 3.4. The values of 87Sr/86Sr in the dental enamel are 0.708400–0.708433, whereas in bones they are 0.708149–0.708471 (±1σ 0.000016–0.000034). Conclusions: The Illyrian community on the island of Korčula relied primarily on agriculture for their food, consuming only cereals, vegetables, and meat from domesticated animals. They did not extensively use marine resources. They were in good health generally. The individuals examined were native residents of the island and can be associated through their dental morphology with the Western Eurasian population group. The average lifespan of the population corresponds to the typical life expectancy during the Late Iron Age.